ACCOUNTABILITY AND TRANSPARENCY OF DISTRICT FINANCIAL REPORTS - Irawan; Ilham Ramdhan Nasution; Ahmad Sani (International Journal of Management, Economic and Accounting, 2025)
The purpose of this study is to explain and describe the accountability and transparency of sub-district financial management from the planning, implementation, administration, and accountability processes. This research design uses a qualitative approach with in-depth interview instruments with sources who have competence in their fields. Based on the results of the research analysis, it can be concluded that accountability in the sub-district government has been implemented in accordance with the Minister of Home Affairs Regulation Number 113 of 2014, which includes planning, implementation, administration, reporting, and accountability. The obligation to account for financial reports and budget realization has been carried out through APBD reporting which is reported directly to the Medan City Government at the end of each month and semester 1 and semester. Transparency has been well-established, with every activity reported on an application provided by the Medan mayor. Sub-districts implement the principle of transparency in financial reporting through the LKPP application, which is uploaded directly by the Medan City Government, allowing the public to access all of the data.